THE PORTRAIT OF INSPIRING ENGLISH LECTURERS IN ENGLISH DEPARTMENT, FACULTY OF LANGUAGES AND LITERATURE, STATE UNIVERSITY OF MAKASSAR BASED ON STUDENTS PERCEPTION - Nurqalbi, Nurqalbi; Samtidar, Samtidar; Sakkir, Geminastiti (State University of Makassar, 2022)
This research aims to determine students perception of inspiring English lecturers and portrait of inspiring English lecturers in English Department, Faculty of Languages and Literature, State University of Makassar. The researcher applies mixed-methods research to achieve the research objectives. The data was collected in the form of a Likert questionnaire and interviews. The subjects of this study were students in the 2019 English Language Education Study Program. The sample questionnaire had 35 students, and the interviews were with 5 students who were taken using a voluntary sampling technique. Data analysis findings revealed that students' perceptions of portraits inspiring English lecturer with a classification. 20% of students were classified as very positive, and 80% of students were classified as positive, and no students had moderate, negative, or very negative perceptions. (2) Based on the data from students interviews, an inspiring English lecturer is one who provides motivation, feedback, appreciates students, punctuality, cares, has English language skills, good teaching strategies, firm and disciplined. Therefore, it can be concluded that students think that the English lecturer in the English department is an inspiring English lecturer. Keywords— Inspiring English Lecturers, Students’ Perception